Mystery of the Treatment of Syphilis - T S Rajashekar; Kumar K Suresh; E Meghana; T R Pavithra; Chowdary Y Deepthi; K Hanumanthayya (Journal of Clinical and Biomedical Sciences)
Syphilis is the commonest sexually transmitted disease (STD) affecting humans globally. On 12.10.1492, Christopher Columbus with his crew landed in Haiti (America) and returned to Spain (Europe) on 15th March 1493. Historians believe that, he and his crew members spread the disease syphilis in Europe, which he and his crew members had contracted in Haiti. The migration of people due to war (soldiers and mercenaries), merchants and slave trade contributed to the rapid spread of the disease and it became a pandemic. Initially, syphilis was highly contagious and virulent, affecting millions of people with very high mortality. Hence, the physicians of that time left no stone unturned for finding a cure. They tried mostly ineffective and harmful methods to treat syphilis. The drugs proved to be more harmful than curative. The fatality due to drugs itself was very significant. Alexander Fleming, a Scottish physician discovered penicillin in 1928 as a crude extract from Penicillium rubens. Eagle H and his coworkers in 1940, found that, penicillin at a relatively low dosage used over a prolonged period of four weeks cured syphilis. The discovery of penicillin enabled to transform a disease with high mortality to a manageable disease. Keywords: Syphilis, Treponema pallidum, Infectious disease